Improvements in mother-child health indicators in Turkey - Akın, Ayşe; Köseli, Arzu (The Turkish Journal of Pediatrics, 1997)
Turkey has a young population as a result of high fertility and growth rates in the recent past. Thirty-five percent of the population is less than 15 years of age, and 25 percent of the population comprises reproductive-age woman. The latest estimate of the population growth rate was 19 per thousand for the 1990-1995 period. In recent decades dramatic declines in fertility rates have been noted. In the early 1970s, the overall fertility rate was approximately five children per woman, declining to 2.7 in 1993. The crude birth rate is currently estimated to be approximately 23 per thousand. The crude death rate has also declined from approximately 30 per thousand in the 1940s to 6.5 per thousand in the 1990s. Life expectancy at birth in Turkey is 65.9 for males and 70.5 for females. The infant mortality rate in the 1960s was approximately 200 per thousand, declining to 67 per thousand during the 1985-1990 period, and 53 per thousand for the period 1988-1993. It was 48 per thousand in 1995 and 42.2 per thousand in 1996, according to the State Planning Organization. The infant mortality rate has declined by 35 percent in the last ten years. The mortality rate for children under five years of age was 113.5 per thousand between 1978-1983 and 60.9 per thousand in 1993; it is currently 50 per thousand. The maternal mortality rate was greater than 200/100,000 in 1995. During the last five years the proportion of women receiving antenatal care has increased from 43 to 63 percent. The proportion of safe deliveries was 76 percent. Thirty-nine percent of all deliveries occur at home. The important point here is that the proportion of unsafe deliveries assisted by traditional birth attendants is 24 percent. It is very obvious that during the last 15 years, maternal and child health (MCH), especially child health, has improved dramatically in Turkey. The improvement made in the last five years has been more marked. The improvement is closely related to the government’s special interest, attention and efforts to prevent and identify the most common health problems and to overcome these problems with appropriate interventions. The government also pays special attention to the socio-economic priority areas of the country and initiates special health programs in these areas first, in order to reduce high regional differences in MCH indices. Despite these dramatic improvements, one great obstacle is the high maternal and infant mortality and morbidity rates in the country at the time of ratification of the European Social Charter. The success made so far in maternal and child health should not be ignored, but it must be realized that much still remains to be done to improve the MCH level further.